Experimental comparative study of a novel drug-eluting arteriovenous graft in a sheep model - Riber, Sara Schødt; Clausen, Lene Langhoff; Dahl, Marie; Riber, Lars Peter Schødt; Andersen, Thomas Emil; Lindholt, Jes S. (Frontiers in Cardiovascular Medicine, 2024)
Background: Arteriovenous (AV) grafts often develop severe complications of stenosis due to neointimal proliferation that occurs either at the venous anastomosis site or at the outflow receiving vein. Thrombosis and infections can then result due to the repeated punctures necessary for dialysis. These complications in turn reduce the durability of the AV graft. This study compares primary patency during 12 months of follow up for a new experimental Biomodics © interpenetrating polymer network (IPN) drug-eluting graft prototype with state-of-the-art GORE ® ACUSEAL (ACUSEAL) in an AV graft model in sheep.An end-to-end bypass from the common carotid artery to the jugularis vein was performed bilaterally in 12 sheep. The usage of GORE ® ACUSEAL ACUSEAL or the e Biomodics © IPN IPN, (both 6.0 mm in diameter,) was determined via randomization. The sheep were followed up every 4 weeks with ultrasonic duplex scanning to determine patency; the experienced observer was blinded to the randomization. One sheep died after 11 days, and the final sample accordingly consisted of 11 animals. When comparing neointimal hyperplasia after 12 months in the two graphs, Fisher's exact test showed a significant difference with none out of 11 in the IPN grafts and 9 out of 11 in the ACUSEAL graft (p<0.001)Repeated measures ANOVA of primary patency revealed no significant differences after 12 months. However, the Biomodics © IPN exhibited severe deterioration over time.Conclusions: Almost all of the grafts occluded during the 12 months of follow up. Although the zwitterion-bounded interpenetrating drug eluting polymer network showed signs to impair neointimal hyperplasia and thrombosis, age-related degeneration hindered demonstrating a potential improvement in patency.Interpenetrating polymer network drug-eluting grafts have the potential to improve the patency of grafts, but the problem of deterioration needs to be solved.